Tinnitus Patients with Comorbid Headaches: The Influence of Headache Type and Laterality on Tinnitus Characteristics - Langguth, Berthold; Hund, Verena; Landgrebe, Michael; Schecklmann, Martin (Frontiers in Neurology, 2017)
Background: Both clinical experience and clinical studies suggest a relationship between tinnitus and headache. Here we aimed to investigate the influence of co-morbid headache type and headache laterality on tinnitus characteristics. Method: The Tinnitus Research Initiative database was screened for patients of the Tinnitus Center of the University Regensburg who reported co-morbid headaches. These patients were contacted to complete additional validated questionnaires. Based on these data patients were categorized according to headache type and headache laterality and their clinical characteristics were compared with tinnitus patients, who did not report co-morbid headaches. Results: Data from 193 patients with tinnitus and co-morbid headaches were compared with those from 765 tinnitus patients without co-morbid headaches. Tinnitus patients with co-morbid headache have higher scores in tinnitus questionnaires, a lower quality of life and more frequently comorbidities such as painful sensation to loud sounds, vertigo, pain (neck, temporomandibular, and general) and depressive symptoms as compared to tinnitus patients without headaches. Both headache laterality and headache type interact with the degree of co-morbidity with higher impairment in patients with left-sided and bilateral headaches as well as in patients with migraine or cluster headache. Conclusion: The observed increased impairment in tinnitus patients with co-morbid headache can be explained as an additive effect of both disorders on health-related quality of life. The more frequent occurrence of further co-morbidities suggests a generally increased amplification of sensory signals in a subset of tinnitus patients with co-morbid headaches.